Physical and Chemical Changes of New Zealand Abalone (Haliotis iris) With Pulsed Electric Field (PEF) Processing and Heat Treatment - Luo, Qian (Auckland University of Technology, 2018)
Haliotis iris is an endemic species of abalone in New Zealand. With limited domestic market, New Zealand abalone is mainly exported in frozen, chilled and vacuum-packed forms. Pulsed electric field (PEF) is a non-thermal technology for food preservation that retains food quality attributes and nutritional value. The objective of this study was to examine the physical and chemical changes of abalone meat after 1) PEF processing at different pulse intensity levels of 0.66 kV/cm, 1.38 kV/cm and 2.00 kV/cm, 2) heat treatments at 70 °C, 80 °C and 90 °C for 15 min, and 3) PEF processing at different pulse intensity levels followed by heat treatments. Each abalone sample was cut in half, with one half used for three different PEF treatments, and the other half as non-PEF treated controls. Unheated abalone were used to compare the differences between both non-PEF treated controls and PEF treated samples before and after heat treatments. Changes in instrumental color, texture profile, free amino acids (FAAs), fatty acids (FAs) and 2-thiobarbituric acid reactive substances (TBARs) values with the different treatments were determined to evaluate the physical and chemical properties of abalone meat. In general, 0.66 kV/cm, 1.38 kV/cm and 2.00 kV/cm PEF treatments had almost no significant effects (p > 0.05) on color, texture, TBARs value, FFAs and FAs content of unheated samples compared to the non-PEF treated controls without heat treatment. On the other hand, heat treatment significantly (p < 0.05) changed meat color, as well as increased toughness and elasticity, lipid oxidation, and FAAs and saturated fatty acids (SFAs) content of non-PEF treated sample compared to the non-PEF treated control without heat treatment. Only for color analysis, foot and adductor muscles were analyzed separately because of the visual color differences of the muscles, which were deep green and off white in color respectively. Heat treatments at 70 °C, 80 °C and 90 °C of non-PEF treated control adductor muscle caused significant increases in the *L, *a and *b values (p < 0.05) compared to the non-PEF treated control without heat treatment. However, *a and *b values of non-PEF treated foot muscle were significantly higher (p < 0.05), while *L values were significantly lower (p < 0.05) compared to the non-PEF treated control without heat treatment. All texture profile analysis (TPA) values of non-PEF treated control increased significantly (p < 0.05) after 70 °C, 80 °C and 90 °C treatments compared to the non-PEF treated control without heat treatment. With heat treatments on non-PEF treated sample, only cohesiveness and resilience values of 90 °C treatment was significantly higher (p < 0.05) than the 70 °C treatment. Almost all FAAs content of non-PEF treated control except for glutamic acid (Glu) increased significantly (p < 0.05) after 90 °C treatment compared to non-PEF treated control without heat treatment. The total FAs content and total SFAs content of non-PEF treated samples after 70 °C, 80 °C and 90 °C treatments increased significantly (p < 0.05) compared to non-PEF treated control without heat treatment. Only total monounsaturated fatty acids (MUFAs) content of non-PEF treated sample after 70 °C treatment decreased significantly (p < 0.05) compared to non-PEF treated control without heat treatment. The TBARs values of non-PEF treated samples after 80 °C and 90 °C treatments were significantly higher (p < 0.05) than non-PEF treated control without heat treatment and non-PEF treated sample after 70 °C treatment. Abalone samples treated with PEF followed by heat treatments at 70 °C, 80 °C and 90 °C, showed almost no significant differences in color, texture, TBARs value, FFAs and FAs content compared to corresponding non-PEF treated control treated at 70 °C, 80 °C and 90 °C. On the other hand, the changes in color, texture, TBARs value and FFAs content between non-PEF treated control and PEF treated samples after heating at 70 °C, 80 °C and 90 °C were similar. However, there were less significant changes in FAs content in PEF treated samples after heat treatments compared to non-PEF treated control after heat treatments. These findings suggest that heat treatments alone influenced abalone muscle more than PEF treatments alone in terms of the changes in physical and chemical characteristics of abalone meat.
Keywords: Abalone; Pulsed electric field; Heat treatment; Free amino acids; Fatty acids